Systematic Literatur Review (SLR): Pengaruh Determinan Kompetensi, Financial Reward dan Pertimbangan Pasar Kerja terhadap Minat Gen Z Berkarir Dibidang Perpajakan - Kisri Endang; Nayla Sofiatun Nadifa; Dien Noviany Rahmatika (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research examines how Gen Z's interest in career taxation is influenced by competency decisions, financial incentives, and labor market factors. This research uses the SLR (Systematic Literature Review) method which includes collecting, reading, analyzing and sorting literature to identify important findings related to interest in a career in taxation. Using the selection criteria above, the author found 102 journals, then the author filtered the search by limiting the publication year of each journal to 2017 to 2024 and obtained 59 journals. Then the author extracted several journals as samples that were appropriate to the topic being researched, so that the author had collected 50 previous journals that met the author's and research criteria. The results of this research have implications for organizations and policymakers seeking to attract and retain Gen Z talent in the tax field. This research shows that ability assessments and financial incentives have a positive influence on Generation Z's interest in choosing a career in the tax sector, but consideration of labor market conditions plays a different role.